A comparative study of the domain wall motion in ferrimagnets (Fe, Co)1−x(Gd, Tb)x. Issue 37 (30th August 2022) - Zhou, Yuqing; Xu, Teng; Liang, Xue; Zhao, Le; Zhou, Heng-An; Wang, Zidong; Jiang, Wanjun; Zhou, Yan
Abstract : Our work reveals the distinctive DW dynamic behaviors in different RE-TM ferrimagnetic materials. The results show that Gd-based ferromagnets are more suitable for achieving ultrafast DW motion and developing spintronic memories and logic devices. Abstract : Magnetic domain walls (DWs) in rare-earth-transition-metal (RE-TM) ferrimagnetic alloys can be used as information carriers in nonvolatile spintronic devices. Due to the rich combinations of RE-TM elements (such as CoGd, FeGd, CoTb, and FeTb in our case), it is intriguing to reveal the characteristics of DW dynamics in these wide choices of RE-TM compounds. Through a systematic study of the DW motion in thin films with different compositions of stacking order Pt(3 nm)/(Fe, Co)1− x (Gd, Tb) x (∼8 nm)/Ta(3 nm), we show that the partially compensated ferrimagnets CoGd and FeGd can exhibit a faster DW motion under various (in-plane and out-of-plane) magnetic fields driven by current-induced spin–orbit torques. In stark contrast with the fast motion of domain walls in Gd-based ferrimagnets, we find that the CoTb system exhibits much slower DW dynamics, and the FeTb system shows no motion, but evolved into a multi-domain state upon applying current pulses. Our results demonstrate that ferrimagnets CoGd and FeGd are more suitable candidates for achieving ultrafast DW motion, which could be useful for developing spintronic memory and logic devices.